Law and Literature in the 21st Century: The Mexican Case - Jiménez Moreno, Manuel de J. (2025)
This article provides a bibliographic review of the interdisciplinary relationship between law and literature in Mexico during the present century. The movement, which emerged on the continent in the midtwentieth century, has now developed a significant body of literature that attests to the relevance of this current within our legal tradition. Despite this, in the Mexican case there is a notable lack of exhaustive reviews of the specialized literature that would allow for reflection on its evolution. In light of this circumstance, the present research seeks to reflect upon and analyze the bibliographic production of the twenty-first century, that is, from 2000 to 2024. To this end, the production is first contextualized within the regional framework, after which the review is carried out. Following the application of analytical and hermeneutic methodology, it is concluded that the surge in the national production of books on the subject published during the first quarter of the twenty-first century not only demonstrates editorial interest and academic proliferation around the topic, but also the development of research lines by specialists. All of this contributes to the gradual consolidation of the movement in the region and, particularly, within the Mexican intellectual field.